ANALISIS PENGARUH KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Pada Karyawan Bank Indonesia Kantor Perwakilan Purwokerto) - Rini, Gita Setya; Rahardjo, Mudji (Diponegoro Journal of Management, 2014)
Banking industry now faced with the situation of intense competition and rapid change in business dynamics. As evidenced by a large number of banks standing in Indonesia at the moment. Some behavior that is done in companies today not only appropriate role behavior, but more expected to bring up the Organizational Citizenship Behavior (OCB). Organizational Citizenship Behavior (OCB) is an attitude arising among them due to its high organizational commitment. Therefore, by increasing organizational commitment affect Organizational Citizenship Behavior (OCB) among employees. This purpose of this study aims to analyze the influence of organizational commitment on the Organizational Citizenship Behavior (OCB). The sample in this research are permanent employees which amounts to 44 respondents by the census method. Methods of data collection in this study was through a questionnaire that distributed to 44 employees in Bank IndonesiaÂ  representative office of Purwokerto .The analysis showed that variable organizational commitment have a positive affect on Organizational Citizenship Behavior. The coefficient of determination indicates Adjusted R Square of 0,563. The results of the determination coefficient indicates that the contribution of organizational commitment in influencing Organizational Citizenship Behavior is 56,3% while the remaining 43,7% is influenced by other variables. It can be conclude that, organizational commitmentÂ  have a strong influence in affecting Organizational Citizenship Behavior.